An analysis of diets among patients with gastrointestinal disorders and a comparison of treatments, supplement use, and symptoms in Inflammatory Bowel Disease compared with other gastrointestinal disorders at Kenyatta National Hospital, Kenya - Onono, Rebecca Kivuli; Munene, Stella Makena; Thiauru, Lawrence Mugambi; Mapesa, Job Okoko (World Nutrition, 2025)
BackgroundInflammatory Bowel Disease (IBD) is a chronic gastrointestinal disorder (GD) in which both pharmacological treatment and dietary practices may influence symptom control, nutritional status, and disease progression. Dietary practices are integral to symptom management in IBD, yet context-specific data from sub‑Saharan Africa are limited.ObjectiveThis study aims to compare medication use, self-imposed dietary restrictions, and nutrition-related care between patients with IBD and those with other gastrointestinal disorders, to examine how these factors are associated with common symptoms. In addition, we describe patient-reported dietary intake patterns.MethodsWe conducted a hospital‑based cross‑sectional study at Kenyatta National Hospital (KNH). Adults (≥18 years) with confirmed IBD (n=40) and with other GD (n=79) were enrolled. Data were collected via structured questionnaires and records review. Analyses used descriptive statistics and χ²/Fisher’s exact tests (two‑sided, α=0.05).ResultsUse of core IBD pharmacotherapy was higher in IBD than GD (100% vs 75.3%; p